PENGAWASAN KINERJA ADVOKAT DALAM PEMBERIAN BANTUAN DAN PELAYANAN JASA HUKUM (STUDI DI JAWA TENGAH) - Agus Raharjo; Angkasa Angkasa; Hibnu Nugroho (Faculty of Law, Universitas Jenderal Soedirman, 2014)
The performance of advocate simply defined as the effectiveness of the services provided by advocates and efficiency of resources allocated and used to prepare such services. There are several reasons that make the effectiveness of the performance advocate can not be determined as exact. Research that seeks to find and locate the causes of the use of empirical legal research methods with sociological and economics approach. The indicators of performance can be classified into several types, namely efficiency, effectiveness, cost-effectiveness and impact indicators. Based on the results of a study of lawyers, law firm/law office or legal aid organizations in Central Java, a performance indicator has not been implemented fully and consistently. They have not implemented a process-oriented quality management as an end result of legal services. Orientation is still focused on the principle of win-lose in handling criminal cases, and management principles are ignored. Transparency as a precondition for performance measurement is also difficult to obtain. This happens because the oversight of the work of da n their performance is still very weak. Keywords: advocate, performance, legal services, legal aid